2016
DOI: 10.1186/s12876-016-0532-2
|View full text |Cite
|
Sign up to set email alerts
|

Changes in plasma ghrelin and leptin levels in patients with peptic ulcer and gastritis following eradication of Helicobacter pylori infection

Abstract: Background Helicobacter pylori (H. pylori) infection and eradication therapy have been known to influence gastric ghrelin and leptin secretion, which may lead to weight gain. However, the exact relationship between plasma ghrelin/leptin levels and H. pylori infection has remained controversial. The aim of this study was to investigate plasma ghrelin and leptin levels in H. pylori-positive and -negative patients, to compare the two levels of the hormones before and after H. pylori eradication, and to examine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 45 publications
3
19
0
1
Order By: Relevance
“…We conducted this study to evaluate the presence of an association, in dyspeptic patients, between persistent H. pylori infection, the genotype of infecting strain, the type of gastric pathology, and the serum ghrelin and leptin levels in patients with a measured anthropometric nutritional status. Our study demonstrated that H. pylori infected patients had lower serum ghrelin concentrations than the uninfected ones, independently of their BMI or gender, supporting the findings from several groups[ 12 - 14 , 17 , 35 ]. It has been demonstrated that ghrelin exhibits gastroprotective antioxidant and anti-inflammatory effects[ 36 - 38 ], modulating gastric mucosal inflammation induced by H. pylori lipopolysacaccharide (LPS) through several mechanisms which were recently reviewed[ 39 ].…”
Section: Discussionsupporting
confidence: 89%
“…We conducted this study to evaluate the presence of an association, in dyspeptic patients, between persistent H. pylori infection, the genotype of infecting strain, the type of gastric pathology, and the serum ghrelin and leptin levels in patients with a measured anthropometric nutritional status. Our study demonstrated that H. pylori infected patients had lower serum ghrelin concentrations than the uninfected ones, independently of their BMI or gender, supporting the findings from several groups[ 12 - 14 , 17 , 35 ]. It has been demonstrated that ghrelin exhibits gastroprotective antioxidant and anti-inflammatory effects[ 36 - 38 ], modulating gastric mucosal inflammation induced by H. pylori lipopolysacaccharide (LPS) through several mechanisms which were recently reviewed[ 39 ].…”
Section: Discussionsupporting
confidence: 89%
“…It has the ability to ferment a large variety of organic substrates, enabling flexible growth in the colon. Different bacterial species in the Blautia genus have been associated with obesity [74]. There is an association between Blautia and human genetic variants in a genomic region that has been associated with obesity and BMI [75].…”
Section: Short-chain Fatty Acidsmentioning
confidence: 99%
“…study, H. pylori infection and the brevity of the period from gastrectomy to PD may have affected the delayed recovery of plasma ghrelin. Suppression of plasma ghrelin has been reported in patients with H. pylori (28). Takachi et al (10) indicated the possibility of compensatory ghrelin production in the remnant stomach and duodenum.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is the insufficient extraction of factors that affect ghrelin production and feedback. In addition to nutrition and inflammation, H. pylori infection and cachexia status affect ghrelin production (28,39,40). These factors cannot be ignored because the rate of H. pylori infection is higher in Japanese people, and the progression of pancreatic and biliary carcinoma is strongly related to cachexia (41,42).…”
Section: Univariate Multivariate ------------------------------------mentioning
confidence: 99%